Optimizing residential heating and energy storage flexibility for frequency reserves. (September 2018) - Kilkki, Olli; Seilonen, Ilkka; Zenger, Kai; Vyatkin, Valeriy
Highlights: Residential houses equipped with energy storages are studied for application in frequency reserves. A distributed price-based optimization framework is proposed. Simulations suggest that the proposed scheme could provide financial incentives for reserve participation. Abstract: The increase in intermittent renewable generation motivates participation of also the electricity consumers in maintaining the production–consumption balance of the electrical grid. This paper proposes a distributed price-based optimization scheme for involving a population of consumers in day-ahead procurement of electricity and frequency containment reserves. Energy storage charging and heating of residential houses are planned before the operating day, while taking into account uncertainties in the day-ahead electricity and reserves markets, weather conditions, and realized frequency. The proposed approach is formulated as stochastic quadratic programming problems and coordinated using a parallelized formulation of the alternating direction method of multipliers (ADMM). Chance constraints for the storage state of charge variations under uncertain reserve activation are formulated as second-order cone constraints. The numerical results illustrate the potential benefits of including consumers in the optimization of reserves.